Navigating Poster Design in the Sea of SoTL - Schrum, Kelly; Mills, Emma; Fong, Wai Ling; Chick, Nancy (Teaching and Learning Inquiry, 2025)
In 2023, Teaching & Learning Inquiry (TLI) began accepting ISSOTL conference poster submissions for peer review and publication (TLI n.d.-a). ISSOTL developed peer review guidelines (TLI n.d.-b) with the goal of elevating scholarly communication in new and engaging ways. These guidelines outline basic principles of design to guide researchers in developing scholarly posters that are simple, clear, and effective for an international, interdisciplinary SoTL audience. Grounded in research and scholarly communication best practices (Chick 2025; Johnson 2014; Literat et al. 2018; Manarin 2016; Morrison 2020; Schrum et al. 2022), the TLI peer review guidelines (TLI n.d.-b) suggest that a poster must tell a complete story such that its main messages are informative on their own. Distilling scholarly research into an engaging visual narrative, however, can be challenging without design skills or visual communication experience (Gundogan et al. 2016; Schrum 2022). This poster presents basic design principles for communicating complex SoTL research in concise and visually appealing ways in order to tell your SoTL story effectively. This work aligns closely with the ISSOTL 2024 conference theme, Recognizing Impact and Reinvigorating Practice (ISSOTL 2024), and the foundational questions regarding what SoTL is and might be (Hutchings 2000). The poster encourages SoTL scholars to envision and construct new ways of communicating SoTL that they can put into practice while learning valuable, transferable skills (Oliver and Jorre de St. Jorre 2018). Getting Started One way to get started designing more effective scholarly posters is to explore posters published in TLI, such as those listed below. As you examine these posters, ask yourself key ANCHOR questions: What SoTL story (Halpern 2023) does the poster tell? What is most important for the viewer to consider and take away from the poster? How might different kinds of viewers (e.g., the viewer across the room, the viewer passing by, and the viewer who stops to read closely) engage with it? Example 1: SoTL in Human Movement Sciences: Moving Forward in South Africa. (Schreck et al. 2023). https://doi.org/10.20343/teachlearninqu.11.31 Example 2: Journal Club: An Innovative Teaching Practice to Foster Peer Connection and Enhance Information Literacy Skills. (Croxen, Nelson, and McKendrick-Calder 2023). https://doi.org/10.20343/teachlearninqu.11.30 Example 3: Code Switching as a Teaching and Learning Strategy: Opinions and Perceptions of University-Level Students of French as a Foreign Language (FFL) in Ghana. (Kwaffo 2023). https://doi.org/10.20343/teachlearninqu.11.29 Please note: Our poster is designed to convey information to a range of viewers. The authors recommend zooming in to read all text and visiting the online resources and ANCHOR worksheet https://bit.ly/goodposters2024 for additional information.